The novel HLA‐B13:01:23 allele, identified by Sanger dideoxy nucleotide sequencing in a Chinese individual - Du, Huan; Xie, Zhi‐Cong; Ma, Li; Li, Yu‐Xia; Ma, Fu‐Tian (HLA, 2024)
HLA‐B*13:01:23 differs from HLA‐B*13:01:01:01 by one nucleotide in exon 5.